Upaya Guru dalam Meningkatkan Percaya Diri Anak melalui Bermain Kata untuk Anak Kelompok B TK Aksara Mulia Serua Bojongsari Depok - Ningrum, Desy Ayu; Fachrita, Surya Aini (El-Athfal : Jurnal Kajian Ilmu Pendidikan Anak, 2024)
It is very important to develop self-confidence from an early age, because this is the most important foundation for someone to be able to live successfully and happily throughout their life. Continuous parental love and attention certainly makes a major contribution so that children's self-confidence grows optimally. Apart from that, the environment, social interactions and educators also support the growth of children's self-confidence, having self-confidence helps children to be accepted in their environment. Meanwhile, this research aims to determine teachers' efforts to increase children's self-confidence through playing with words. The formulation of the problem in this research is how do teachers increase children's self-confidence through playing with words? This type of research is descriptive qualitative research, the method used is classroom action research, the model used by researchers is the model proposed by Kemmis and Mc Taggart. The research subjects in the research were students and teachers of group B Kindergarten Aksara Mulia. Data collection techniques in this research are: observation, cycles, interviews and documentation. The results of the research show that the teacher's efforts to increase children's self-confidence through playing with words were successful in increasing children's self-confidence in learning. This can all be seen from the results of observations that each cycle increases. The pre-cycle stage was 23%, cycle 1 was 43%, and in cycle II it increased to 79%. From these results it is concluded that the teacher's efforts to increase children's self-confidence through playing with words in group B children aged 5-6 years at the Noble Literacy Kindergarten can increase children's self-confidence. When playing with words, children become more initiative, dare to appear and are confident in their own abilities. Not only that, learning to play with words also creates a fun and active learning atmosphere